Efficacy and safety of ustekinumab treatment in adults with moderate‐to‐severe atopic dermatitis. Issue 1 (9th August 2016) - Khattri, Saakshi; Brunner, Patrick M.; Garcet, Sandra; Finney, Robert; Cohen, Steven R.; Oliva, Margeaux; Dutt, Riana; Fuentes‐Duculan, Judilyn; Zheng, Xiuzhong; Li, Xuan; Bonifacio, Kathleen M.; Kunjravia, Norma; et al.
Abstract: Atopic dermatitis (AD) is the most common inflammatory skin disease, but treatment options for moderate‐to‐severe disease are limited. Ustekinumab is an IL‐12/IL‐23p40 antagonist that suppresses Th1, Th17 and Th22 activation, commonly used for psoriasis patients. We sought to assess efficacy and safety of ustekinumab in patients with moderate‐to‐severe AD. In this phase II, double‐blind, placebo‐controlled study, 33 patients with moderate‐to‐severe AD were randomly assigned to either ustekinumab (n=16) or placebo (n=17), with subsequent crossover at 16 weeks, and last dose at 32 weeks. Background therapy with mild topical steroids was allowed to promote retention. Study endpoints included clinical (SCORAD50) and biopsy‐based measures of tissue structure and inflammation, using protein and gene expression studies. The ustekinumab group achieved higher SCORAD50 responses at 12, 16 (the primary endpoint) and 20 weeks compared to placebo, but the difference between groups was not significant. The AD molecular profile/transcriptome showed early robust gene modulation, with sustained further improvements until 32 weeks in the initial ustekinumab group. Distinct and more robust modulation of Th1, Th17 and Th22 but also Th2‐related AD genes was seen after 4 weeks of ustekinumab treatment (i.e. MMP12, IL‐22, IL‐13, IFN‐γ, elafin/PI3, CXCL1 and CCL17; P <.05). Epidermal responses (K16, terminal differentiation) showed faster (4 weeks) and long‐term regulation (32 weeks) from baseline in the ustekinumab group. No severe adverse events were observed. Ustekinumab had clear clinical and molecular effects, but clinical outcomes might have been obscured by a profound "placebo" effect, most likely due to background topical glucocorticosteroids and possibly insufficient dosing for AD.